PTU-052 The Impact of Thiopurines on Risk of Intestinal Surgery in Elderly-Onset IBD. (17th August 2016) - Alexakis, C; Saxena, S; Chhaya, V; Cecil, E; Pollok, R
Abstract : Introduction: Thiopurines (TP) have an established role in the maintenance of steroid-free remission in IBD. Their role in reducing the need for surgery in younger populations has been recently highlighed. 1 TPs are associated with an increased risk of lymphoma in the elderly but their role in reducing the risk of surgery in patients with elderly-onset IBD (EO-IBD) is not established. We therefore aimed to evaluate the impact of TPs on the risk of surgery in EO-IBD, using a nationally representative research database. Methods: This was a retrospective descriptive study using data from the Clinical Practice Research Datalink (CPRD). Incident cases of IBD were isolated using previously validated Read codes. Patients were included if they had codes for ulcerative colitis (UC) or Crohn's disease (CD), and their date of diagnosis was on/after their 60 th birthday. Information extracted included sex, age at diagnosis, smoking status, and prescription data for IBD medications. Finally, we obtained data on our main outcomes: colectomy in UC and first intestinal surgery in CD. A multivariate Cox proportional hazard model was generated to deduce the risk of surgery according to TP use. The model was adjusted for potential confounders including sex, smoking, 5 ASA use and early steroid use (corticosteroid within 3 months of diagnosis). In a subgroup of TP users, a second proportional hazard model was used to define the impact of duration of TP treatment on the risk of surgery. Results: 2758 and 1349 were identified with EO-UC and EO-CD respectively, with a mean follow up of 4.9 years. Mean age at diagnosis was 71.8 years. Table 1 demonstrates the summary demographic and prescription data for both groups. TP use was associated with an increased risk of colectomy in EO-UC (HR 3.5, CI 2.28–5.35, p < 0.0001), but not an increased risk of first intestinal surgery in EO-CD. In subgroup analysis restricted to TP users only, TP use for greater than 12 months in EO-UC was associated with a 64% reduction in risk of colectomy (HR 0.36, CI 0.18–0.7, p = 0.003). Similar findings were not seen in EO-CD. Conclusion: TP use for longer than 12 months is associated with a reduced risk of colectomy in EO-UC but in contrast does not appear appear to impact on the risk of first intestinal surgery in EO-CD. This is an important observation since the risk of TP-associated lymphoma is substantially increased in this age group. Further work is needed to evaluate the role of TPs in EO-IBD. Reference: 1 Chhaya V, et al . Impact of early thiopurines in 2770 children and young people diagnosed with IBD: a national population-based study. Aliment Pharmacol Ther . 2015 Oct;42 (8). Disclosure of Interest: C. Alexakis: None Declared, S. Saxena Grant/research support from: SS is funded by a National Institute for Health Research Career Development Fellowship (NIHR CDF-2011-04-048). The views expressed are not necessarily those of the NHS, NIHR, or Department of Health. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript, V. Chhaya: None Declared, E. Cecil Grant/research support from: EC is funded by a National Institute for Health Research Career Development Fellowship (NIHR CDF-2011-04-048). The views expressed are not necessarily those of the NHS, NIHR, or Department of Health. The funders had no role in study design, data collection and analysis, decision to publish, or preparation of the manuscript, R. Pollok: None Declared